Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1021/es940482c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Zeolites from Coal Fly Ash

Abstract: Previous attempts to use fly ash as a soil amendment have had limited success because of its low nutrient value, low cation exchange capacity (CEC), and elevated levels of toxic trace elements. However, treating fly ash with NaOH or KOH at an elevated temperature converts the ash into zeolite minerals and solubilizes the toxic trace elements, which are removed in the base solution. The CEC of the untreated fly ash was <100 mmolC kg-1 but increased to over 3000 mmolC kg-1 when heated for 3 days at 100 °C in 3 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0
24

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(95 citation statements)
references
References 17 publications
5
65
0
24
Order By: Relevance
“…6) Amrhein et al reported that Ψ-chabazite (K-G zeolite; K2Al2SinO2n+4·xH2O) was formed when FA was treated with 3 mol dm -3 KOH in a capped Teflon tube at 100°C for 3 d. 7) Murayama reported similar results, 8) in which Ψ-chabazite was formed by the treatment of FA with 2 mol dm -3 KOH in an autoclave at 120°C for 24 h. It is, however, still unclear how FA-derived zeolite phases change depending on synthetic conditions of the KOH hydrothermal treatment. In the present study, the effects of synthetic conditions of the KOH treatment on the formation of FA-zeolite were examined.…”
Section: Introductionmentioning
confidence: 99%
“…6) Amrhein et al reported that Ψ-chabazite (K-G zeolite; K2Al2SinO2n+4·xH2O) was formed when FA was treated with 3 mol dm -3 KOH in a capped Teflon tube at 100°C for 3 d. 7) Murayama reported similar results, 8) in which Ψ-chabazite was formed by the treatment of FA with 2 mol dm -3 KOH in an autoclave at 120°C for 24 h. It is, however, still unclear how FA-derived zeolite phases change depending on synthetic conditions of the KOH hydrothermal treatment. In the present study, the effects of synthetic conditions of the KOH treatment on the formation of FA-zeolite were examined.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 The addition of reaction promoters such as sodium hydroxide (NaOH) and/or potassium chloride (KCl) to enhance the reaction activity in forming zeolite and to improve the adsorption properties by increasing the surface area of synthesized zeolite is quite common. 9,10,13,14 Often the resulting zeolite has negatively charged functional groups on the surface, offering potential sorption applications particularly for the sequestration of cationic metals. 15 In this work, the synthesis of zeolite from the CFA obtained from one of the actual coal-fired combined power plants in Thailand was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the environmental problems presented by the fly ash, considerable research has been undertaken on the subject worldwide. The utilization of fly ash as a low-cost adsorbent and zeolite synthesis for the removal of heavy metals has been studied in several literatures [8][9][10]. Fly ash was found to have a higher adsorption capacity for Cd(II), as Fly ash obtained from the combustion of poultry litter was also utilized as an adsorbent for the removal of Cr(III) from aqueous solution [11].…”
Section: Introductionmentioning
confidence: 99%